ANALISIS PREMI BULANAN ASURANSI JIWA DWIGUNA POLIS PARTISIPASI MENGGUNAKAN SUKU BUNGA MODEL VASICEK - PRAYANA, I WAYAN RISAL ANDI; WIDANA, I NYOMAN; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika, 2023)
Endowment insurance with a participating policy is an insurance contract that offers death benefits that increase every year. This paper analyzes a single and monthly premiums of participating policy endowment life insurance using the Vasicek interest rate model. The increase in benefits is highly dependent on the performance of the insurance company's investment portfolio. The model in this study assumes that market interest rates move stochastically following the Vasicek model and the company's investment portfolio follows the geometric brownian motion (GBM) model. This study assumes that the participant is a man aged 30 years and buys an insurance contract for 20 years with non-participation benefits of Rp. 100,000,000.00. As a result, the premium that must be paid by the man is IDR 37,832,555.84 for a single premium and if the insurance participant chooses to pay monthly, the premium is IDR 240,915.59. The insurance premium with a participation policy is influenced by the participation coefficient, the asset volatility of the investment portfolio, the minimum guarantee interest rate and the entry age of the insurance participant.